PENGARUH GAYA KEPIMPINAN DAN MOTIVASI KERJA TERHADAP LOYALITAS KARYAWAN HOTEL MUTIARA MERDEKA - Aban, Adnan; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of leadership style and work motivation on employee loyalty at the Mutiara Merdeka Pekanbaru Hotel. Employee loyalty is one of the loyalty of employees in the company. To encourage employees to remain loyal to the company, first of all factors must be investigated that affect employee loyalty. For this reason leadership style factors have a role in directing individual behavior including employee work motivation. Leaders who provide calm in work situations and employee motivation can increase employee loyalty. In general, the better the leadership style and work motivation, the more loyal a person is in carrying out his work activities in the company. The population in this study were all employees of the Mutiara Merdeka Pekanbaru Hotel with 52 samples taken using the Slovin formula. The sampling method in this study is in the form of primary data and secondary data using questionnaires, interviews and documents in the company. Analysis of the data used is simple and multiple linear regression using the application SPSS ver 25 for windows.  The results showed that leadership has a positive and significant effect on employee loyalty as evidenced by the value of t 5.247> t table 1.998. Work motivation has a positive effect on employee loyalty to Mutiara Merdeka Hotel employees, as evidenced by the calculated value of 4.110> 1.998 tables.  F test results show that the calculated F value of 18.296> F table 3.14 which means that the leadership style and work motivation significantly influence employee loyalty.  Keywords: Leadership Style, Work Motivation, and Employee Loyalty